PENGARUH KARAKTER EKSEKUTIF, KARAKTERISTIK PERUSAHAAN DAN DIMENSI TATA KELOLA PERUSAHAAN YANG BAIK PADA TAX AVIDANCE DI BURSA EFEK INDONESIA - Fitria Purnamasari, 11.05.52.0167; Wahjudi, Djoko (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to analyze the influence of executive character, laverage, independent directors and audit committee against tax avoidance in companies listed on the Stock exchange Years 2012-2014. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in the period 2012-2014. The sample in this study in many as 75 companies. The sampling technique used purposive sampling. The criteria for the sample in a row during the observation period 2012-2014. Tha analysis tool used is multiple linear regression. The results the analysis cann be clonclude that : Character executives negatively affects tax avoidance. Laverage positive effect on tax evasion. Independent commissioners positive effect on tax avoidance. The Audit committee negatively affect tax avoidance.Keywords: Corporate Characteristics, Executive Character, Corporate Governance, Tax Avoidance